Proceso de atención de enfermería a un paciente con diagnóstico de enfermedad renal crónica que recibe tratamiento de hemodiálisis - Cárdenas Rodas, Bryan Steven (2019)
The current clinical case was made to an adult patient, a 57-year-old male with a medical diagnosis of terminal chronic kidney disease secondary to arterial hypertension, who entered the hemodialysis program which is performed three times a week (Tuesday, Thursday, Saturday) for 4 hours through left venous arteriovenous fistula, hemodynamically unstable during the session which presents edema in lower limbs, arterial hypertension of values 182/73, intense headache, uremic halitosis. Patient during the hemodialysis session shows signs and symptoms, arterial hypotension due to decreased blood volume, nausea, vomiting, lower limb cramps due to the effect of the dialysis machine and his clinical condition. In the review of his personal history we found that the main cause of chronic kidney disease was high blood pressure and in his family history we found that in his family there is a history of diabetes and high blood pressure Chronic kidney disease is a disease of affluent increase, this involves the organs called kidneys which affects the functional unit called nephron, from the physiological point the kidney loses the capacity of the renal functions these are elimination of toxins, elimination of water, production of hormones. Through the nursing diagnosis obtained by the NANDA taxonomy and the nursing interventions that were carried out through the NIC taxonomy to said patient during the different stages of the hemodialysis treatment, the improvement of the patient's clinical status was achieved, the efficacy of the process of nursing care during the stages of hemodialysis treatment